Endometriosis - Marsh, Courtney (IntechOpen, 2021)
This book provides a comprehensive look at endometriosis, a disease affecting 10 percent of reproductive women. It explores risk factors for endometriosis including environmental factors that are shedding light on this disease. It also investigates novel methods for diagnosing and treating pain related to endometriosis, which can be debilitating in some women. Conditions associated with endometriosis including adenomyosis, invasion of endometrial glands and stroma into the uterine muscle, and infertility are reviewed in depth. Finally, the book examines treatment options for women with endometriosis ranging from hormonal to surgical. This volume is targeted to practitioners seeing patients with endometriosis to better inform them regarding up-to-date diagnostic and treatment options.